Obesity and its influence on cancer: a recent literature review - Freitas, Carolina (2021)
Introduction: Obesity rates have increased worldwide, and this condition is currentlyrecognized as the main preventable cause of various types of cancer. Objective: Therefore, anattempt was made to survey of clinical characteristics that relates obesity and different typesof cancer, between the years 2017 and 2020. Materials and Methods: Integrative literaturereview, with searches for analysis in the PubMed, Scielo and LILACS databases, specificguiding question was: "What is the influence of obesity in relation to different types ofcancer?". Results and Conclusions: 32 articles were indentified, and then 8 were selected.Body fat was emphasized as a factor of important impact in the development of neoplasia. Thedata suggest that four of 10 types of cancer are preventable through changes in the individual'sbehavior and eating pattern. Epidemiological studies have shown a strong link between thedietary factor and the incidence and prognosis of cancer. Considering that diet and exercise aremodifiable factors, primary care projects and interventions are essential for disease prevention Understanding the biological mechanisms explains how healthy behavior promotes improvements, highlighting the importance of disseminating information to risk populations and implementing strategies that help patients make better and healthier choices.